Nilai Akhlak Empati dalam Novel Negeri 5 Menara - Hoeriyah, Umi; Ratri, Rose Kusumaning (IAINU Kebumen, 2024)
Morals play an essential and fundamental role in humans which is used as a theme in the novel. One novel that contains the moral value of empathy is the novel Negeri 5 Menara by Ahmad Fuadi. This research examines the issue of the moral value of empathy in the novel Negeri 5 Menara. The aim of this research is to determine the moral value of empathy in the novel Negeri 5 Menara. This research uses a qualitative literature study type approach. The subject of this research is original data from the novel Negeri 5 Menara by Ahmad Fuadi, the Al-Qur'an, various literature such as journals, books, internet sites, and relevant research. The data collection technique used is a document review technique or documentation study. The data analysis technique used is content analysis. Based on the research results, it can be concluded that there are ten moral values of empathy in the novel Negeri 5 Menara. The ten moral values of empathy include: showing social sensitivity or understanding other people’s feelings, showing sensitivity to other people’s needs and feelings, understanding other people correctly from their body posture, body language, facial expressions and tone of speech, understanding the expressions shown by other people and giving the right reaction, understanding other people’s sadness and giving the right response, showing that he understands other people’s feelings, shedding tears or being sad when other people are sad, showing concern when other people are treated unkindly and unfairly, showing desire to understand other people’s points of view, and verbally express understanding of other people’s feelings